KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI KAWASAN HARAPAN RAYA KOTA PEKANBARU - Mella Frisdianti; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study is aimed to determine and describe the children's identity as the victims of exploitation, and the functioning of their families in the Harapan Raya area in Pekanbaru City. This research is a qualitative study that is descriptively described. The subjects in this study were 6 children who were exploited in the Harapan Raya area. The data were collected based on the observation and structured interviews. The results showed that generally the children victims of exploitation on Jalan Harapan Raya were female, aged 9-13 years, and had a status as the students of elementary school. With the following physical characteristics: thin and short body, brown, dull skin, reddish-black hair, unpleasant body odor, yellowish teeth, wearing flip-flops, a headscarf, with simple and shabby clothes. The functioning of the families of children who are victims of exploitation on Jalan Harapan Raya, in general, has not been maximized. From the seven functions of the family, not all of them can be carried out by every family of the children victims of exploitation.Key Words: Function Of The Family, The Victims Children Exploitation